Cytology and mating systems in the climbing cacti Hylocereus and Selenicereus - Lichtenzveig, Judith; Abbo, S.; Nerd, A.; Tel-Zur, N.; Mizrahi, Y. (Botanical Society of America, 2000)
Chromosome numbers and meiotic behavior are reported for the climbing cacti species Hylocereus undatus, Hylocereus polyrhizus, and Selenicereus megalanthus. The Hylocereus spp. are diploid (2n 5 22), while S. megalanthus is a tetraploid (2n 5 44). Irregular chromosome disjunction at anaphase I in pollen mother cells of S. megalanthus is probably the major cause of its reduced pollen viability and may contribute to low seed set, low number of viable seeds and, consequently, low fruit mass. A pollination study confirmed self-incompatibility in H. polyrhizus and a weakened incompatibility reaction in H. undatus and S. megalanthus. Major crossability barriers do not exist between the Hylocereus spp. investigated. Reciprocal intergeneric crosses were successful between Hylocereus spp. and S. megalanthus, suggesting that an Hylocereus sp. Might be one of the diploid progenitors of the tetraploid S. megalanthus. The implications of the results on cacti nomenclature and systematics are briefly discussed.